Dna quantities and qualities from various stages of some trematodes using optical and HAT-RAPD methods - Wongsawad C. (2014)
The aim of this experiment was to minimize DNA quantity and quality for detection by optical (spectrophotometer at 260 nm and 280 nm) and HAT-RAPD methods. Total DNA from different stages, adult, metacercaria and eggs of 6 trematode species were isolated for analysis. In this experiment, the adult trematodes were classified into 3 groups by size: small, Haplorchis taichui and Stellantchasmus falcatus; medium, Opisthorchis viverrini and Ganeo tigrinus; and large, Paramphistomum epiclitum and Fischoederius elongatus. The adult minimal DNA quantities and qualities of all specimen samples detected by optical method were 97.22,72.28, 3,167.00, 1,490.62, 21,382.66, and 27,321.77 ng; eggs were 3.92, 3.57, 3.72, 6.23, 17.53, and 14.01 ng, respectively; and metacercarial stages 50.70 and 40.98 ng in H. taichui and S. falcatus. In addition, the HAT-RAPD technique was chosen to amplify the minimal DNA qualities and quantities of all trematode specimens. Total DNA was 1-1 x 10(-12) ng; DNA templates in each dilution were used for amplification by primer OPA-09. DNA concentrations ranging between 1 x 10(-8) and 1 x 10(-11) ng were amplified with high polymorphism. Our experiment concluded that only a single specimen of each egg, metacercaria, or adult stage could be amplified with distinct bands.